Penerapan Metode Image Streaming pada Pembelajaran Menulis Teks Cerita Siswa Kelas X SMA PGRI 2 Palembang - Rimba Hati; Liza Murniviyanti; Juaidah Agustina (Pusat Riset dan Inovasi Nasional, 2025)
Short stories are a type of short prose work that is imaginative. Short stories only have one plot, one theme, and character characters. Therefore, the difficulty of peseta didik that often arises in learning the skill of writing short story texts is the difficulty of plot and theme. The problem in this study is how to apply learning to write short ceita texts through the image streaming method in grade X students of SMA PGRI 2 Palembang. The purpose of this study is to find out the application of learning to write short story texts through the image streaming method in grade X students of SMA PGRI 2 Palembang. The method of this research is a quantitative experiment. The results of this study show that the image streaming method has the application of the image streaming learning method in learning to write short story texts in grade X students of SMA PGRI 2 Palembang in learning outcomes. Therefore, the image streaming learning method can be applied in Indonesian learning.